Assessment of adeno-associated virus gene therapies efficacy on acid alpha-glucosidase restoration and glycogen storage correction in cardiac muscle of Pompe disease mice using synchrotron infrared and ultraviolet microspectroscopies - Laurence Dubreil; Lydie Lagalice; Johan Deniaud; Antoine Sabourin; Claire Lovo; Karim Bey; Juliette Hordeaux; Chantal Thorin; Christophe Sandt; Frédéric Jamme; Marie-Anne Colle (Journal of Spectral Imaging, 2019)
Pompe disease (glycogen storage disease type II) is a lysosomal storage disorder due to a mutation in the gene that encodes acid alpha-glucosidase (GAA). GAA deficiency causes the excessive storage of lysosomal glycogen in many cell types, leading to cell and, subsequently, tissue dysfunction. Cardiac, respiratory and skeletal muscles are the most severely affected. Enzyme replacement therapy (ERT) with recombinant human GAA (rhGAA, Myozyme®, Genzyme, Cambridge) is the only approved treatment for Pompe disease. A new therapeutic strategy was developed consisting of delivering adeno-associated virus serotype 9 (AAV9) and serotype 10 (AAV10) vectors expressing human GAA into cerebrospinal fluid of GAA-KO 6neo/6neo Pompe mice. The purpose of this work was to investigate synchrotron Fourier transform infrared (sFT-IR) and deep ultraviolet (sDUV) microspectroscopies to detect new biomarkers of the disease and the AAV gene therapy in the cardiac muscle, one of the most affected organs in Pompe disease. Multivariate statistics applied to sFT-IR spectra between 4000 cm–1 and 950 cm–1 highlighted the potential of sFT-IR to discriminate Pompe (-/-), Wild type and AAV-treated animals from C–H stretching vibrations of CH3, from C–O, C–N and C–C stretching vibrations of amide I, II, III bands and from specific IR signature of the glycogen. Investigations performed by sDUV microscopy showed a significant increase of the tryptophan autofluorescent signal in the right ventricle for the AAV9-treated Pompe mice. The high-resolution sDUV microspectroscopy experiments suggested a correlation between the tryptophan-rich area and the GAA-rich area. These unprecedented results demonstrate that high-resolution UV microspectroscopy can be a complementary innovative approach to monitor the chemical change in label-free cardiac muscle section. Moreover, this non-destructive technology can be applied to a small amount of tissue allowing therapeutic assessment from biopsy of human patients.